Modern views on the pharmacological potential of plants of the genus Salvia: from chemical composition and molecular mechanisms of action to use in clinical practice - Yu. V. Shur; N. A. Sal’nikova; V. Yu. Shur; D. A. Sal’nikova (Сибирский научный медицинский журнал, 2026)
Throughout human history, plants have not only served as a source of beneficial nutrients, but also helped get rid of many diseases. Recently, a consensus has emerged that synthetic components commonly used in the food and pharmaceutical industries can cause a range of illnesses. This has led to a growing global demand for natural and organic forms of medicine, and medicinal herbs and phytomedicines are widely used worldwide as part of supportive therapy for managing pathological conditions. Modern practical medicine employs a significant number of herbal preparations, which possess a number of beneficial properties, such as a low incidence of undesirable side effects, absence of toxic impact on the body, and no risk of dependency upon administration or withdrawal. Plant-based remedies are used both for preventive purposes and in the treatment of diseases, owing to the presence of various biologically active compounds, macronutrients, and micronutrients in their composition. Of undoubted interest as objects of scientific research are plants of the genus Salvia L., which is the largest genus in the family Lamiaceae. This work summarizes and systematizes the literature data on representatives of the genus Salvia, their chemical composition, pharmacological activity and direction of action. Publications containing the results of experimental studies on the chemical components of plants of the Salvia genus, data on various types of their biological activity, as well as molecular mechanisms of action tested in in vitro and in vivo experiments were analyzed.